Detection of insecticide resistance markers in Anopheles funestus from the Democratic Republic of the Congo using a targeted amplicon sequencing panel - Holly Acford-Palmer; Monica Campos; Janvier Bandibabone; Sévérin N’Do; Chimanuka Bantuzeko; Bertin Zawadi; Thomas Walker; Jody E. Phelan; Louisa A. Messenger; Taane G. Clark; Susana Campino (Scientific Reports, 2023)
Abstract Vector control strategies have been successful in reducing the number of malaria cases and deaths globally, but the spread of insecticide resistance represents a significant threat to disease control. Insecticide resistance has been reported across Anopheles (An.) vector populations, including species within the An. funestus group. These mosquitoes are responsible for intense malaria transmission across sub-Saharan Africa, including in the Democratic Republic of the Congo (DRC), a country contributing > 12% of global malaria infections and mortality events. To support the continuous efficacy of vector control strategies, it is essential to monitor insecticide resistance using molecular surveillance tools. In this study, we developed an amplicon sequencing (“Amp-seq”) approach targeting An. funestus, and using multiplex PCR, dual index barcoding, and next-generation sequencing for high throughput and low-cost applications. Using our Amp-seq approach, we screened 80 An. funestus field isolates from the DRC across a panel of nine genes with mutations linked to insecticide resistance (ace-1, CYP6P4, CYP6P9a, GSTe2, vgsc, and rdl) and mosquito speciation (cox-1, mtND5, and ITS2). Amongst the 18 non-synonymous mutations detected, was N485I, in the ace-1 gene associated with carbamate resistance. Overall, our panel represents an extendable and much-needed method for the molecular surveillance of insecticide resistance in An. funestus populations.